The IMF through the lens of Keynesian theory and econometrics: Examples of Ukrainian economic crises in 2008 and 2014 - Ćorić, Domagoj (Oeconomica Jadertina, 2024)
Many economist and academics attribute very negative connotations to the IMF and its stand-by programs. One example is the paper by the authors Chletsos and Sintos (2023). This paper hypothesizes that the assumptions of the negative impact is incorrect and seeks to illuminate the positive consequences of IMF programs and conditionality using the examples of Ukraine's economic crises in 2008 and 2014. To prove this hypothesis, the paper uses Keynesian theory based on the work „The General Theory of Employment, Interest, and Money“, as well as a series of Keynesian modular equations such as: investment multipliers, price elasticity, aggregate investments, user cost, and others. The paper also utilizes Keynesian econometric models for marginal prosperity to consume and marginal efficiency of the capital. The first heading presents a series of academic criticisms directed at the IMF, while the next heading presents Keynesian theory in depth, which serves as the support for the before mentioned econometrics and modular equations. The third heading demonstrates the IMF-Ukraine cooperation during the stand-by arrangement in 2008. Using the previously mentioned econometrics and modular equations, the positive connotation of IMF conditionality is proven in: limiting fiscal spending, restricting monetary policy, and anti-mercantilist measures. In the following heading, the paper shows Ukraine’s acceptance of the IMF program and its implementation, followed by the results. Using Keynesian theory, econometrics, and modular equations, it is proven that the criticisms of IMF conditionality by Chletsos and Sintos (2023) are not supported by empirical evidence. It also shows how the entire program had positive consequences on the Ukrainian economy. The second part of the paper focuses on presenting the causes of the 2014 economic crisis, while the IMF conditionality measures are again justified through Keynesian economic theory and modular equations. After showing Ukraine's implementation of the program, the positive effects of the IMF are demonstrated through econometric models of marginal prosperity to consume and the marginal efficiency of capital. As with the first parto of the paper, the overall review of the 2014 crisis concludes that the IMF measures and conditionality played a postive role for Ukraine’s recovery. The causality of such movement it to be found in the programs close connectivity to Keynesian theory, thus proving thesis of Chletsos and Sintos (2023) to be incorrect.
Keywords: Keynesian theory; Ukrainian economic crisis 2008; Ukrainian economic crisis 2014; stand-by arrangement; IMF